Love Styles dan Kepuasan Hubungan pada Individu dalam Hubungan Pacaran Jarak Jauh - Putri, Rifa Madyana; Ihsan, Helli; Zakariyya, Farhan (Jurnal Psikologi TALENTA, 2024)
ABSTRACTThis research was conducted with the aim of knowing the relationship between love styles and relationship satisfaction in individuals who are in long-distance relationships. This study used a correlational quantitative method with a total of 426 respondents who were in long-distance relationships with age range of 20-35 years. This research questionnaire used the Love Attitude Scale (LAS) and the Relationship Assessment Scale (RAS). The sampling technique uses purposive sampling. Data collection was carried out by distributing questionnaires online via Google Forms. The analysis technique in this study used a correlation test with the help of SPSS software version 25.0 for windows. The results of the study showed that there is a relationship between love styles and relationship satisfaction in individuals who are in long-distance dating relationships. The results of the study showed that there is a relationship between love styles and relationship satisfaction in individuals who went in long-distance relationships with love styles Eros, Storge, Pragma, and Agape had a positive correlation while Ludus and Mania had a negative correlation.Keywords: Long-distance relationship; Love styles; Relationship satisfaction.ABSTRAKTujuan penelitian ini untuk mengetahui hubungan love styles dengan kepuasan hubungan pada individu yang menjalani hubungan pacaran jarak jauh. Penelitian ini menggunakan metode kuantitatif korelasional dengan jumlah responden sebanyak 426 orang yang menjalani hubungan jarak jauh dengan rentang usia 20-35 tahun. Kuesioner penelitian ini menggunakan Love Attitude Scale (LAS) dan Relationship Assessment Scale (RAS). Teknik pengambilan sampel menggunakan purposive sampling. Pengambilan data dilakukan dengan menyebarkan kuesioner secara online melalui Google Formulir. Teknik analisis menggunakan uji korelasional dengan bantuan software SPSS versi 25.0 for windows. Hasil penelitian menunjukkan bahwa terdapat hubungan antara love styles dengan kepuasan hubungan pada individu yang menjalani hubungan pacaran jarak jauh dengan gaya cinta Eros, Storge, Pragma, dan Agape memiliki korelasi positif sedangkan Ludus dan Mania memiliki korelasi negatif.